Intra-arterial Stroke Management - Prince, Ethan A.; Ahn, Sun Ho; Soares, Gregory M. (Seminars in Interventional Radiology, 2013)
Acute ischemic stroke is a leading cause of death and the leading cause of disability in the United States. Cerebral neuronal death begins within minutes after threshold values of blood oxygen saturation are crossed. Prompt restoration of oxygenated blood flow into ischemic tissue remains the common goal of reperfusion strategies. This article provides a brief overview of acute ischemic stroke, a summary of the major intra-arterial stroke therapy trials, and comments on current training requirements for the performance of intra-arterial therapies.
Keywords: ischemic stroke; intervention; thrombolysis; thrombectomy; interventional radiology